2008
DOI: 10.1002/joc.1698
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the large‐scale features associated with the Indian summer monsoon in the recent decades

Abstract: ABSTRACT:The inter-annual variability of the Indian summer monsoon rainfall (ISMR) has been examined in association with the variability of surface temperature, the mean sea level pressure (MSLP), the tropospheric geopotential height, and wind patterns over the globe to study the changes in the large-scale features associated with Indian summer monsoon (ISM) in the recent decades. The data for the study have been considered from 1949-2005 (for a period of 57 years). It has been found that, during the recent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…These wind anomalies are the source of moisture supply over NW India, as they are coming from warm desert land, they can hold more moisture after blowing over north Arabian Sea. Previous study by Yadav (2009a) has shown these relationships between ISMR and Iran surface temperature. The southerlies observed over north Pakistan hinders the intrusion of mid-latitude cold and dry air towards Indian subcontinent favouring excess monsoon over NW India.…”
Section: Relationship Between Nw India Rainfall and Iran Surface Tempsupporting
confidence: 56%
“…These wind anomalies are the source of moisture supply over NW India, as they are coming from warm desert land, they can hold more moisture after blowing over north Arabian Sea. Previous study by Yadav (2009a) has shown these relationships between ISMR and Iran surface temperature. The southerlies observed over north Pakistan hinders the intrusion of mid-latitude cold and dry air towards Indian subcontinent favouring excess monsoon over NW India.…”
Section: Relationship Between Nw India Rainfall and Iran Surface Tempsupporting
confidence: 56%
“…Trenberth et al , ; Alexander et al , ; Deser et al , ). However, the effect of ENSO on SASM has become weaker in the recent decades (Krishna et al , ; Yadav et al , ). Some studies have suggested that the Indian Ocean Dipole (IOD), which has also an influence on SASM (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the dipole surface temperature and pressure anomalies are strongly associated. This dipole structure generates the anomalous northwesterlies over eastern Saudi Arabia, which further combines with the southwesterlies over the Arabian Sea and intensifies the lower‐level monsoon circulation, consistent with the previous studies of Yadav (, , ).…”
Section: Resultsmentioning
confidence: 99%
“…This study, for the first time, shows how the westward enhancement of the Tibetan High imposes a dipole pressure anomaly between Saudi Arabia and Iran, which intensifies the lower‐level monsoon circulation and moisture supply from the Arabian Sea. The anomalous cyclonic circulation with northerly winds over the Arabian landmass has gained its significance after the late 1970s climate shift (Yadav, , , ). This study is certainly going to improve the current understanding of ISM.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation